2023
DOI: 10.3389/fphar.2023.1192423
|View full text |Cite
|
Sign up to set email alerts
|

Does China’s centralized volume-based drug procurement policy facilitate the transition from imitation to innovation for listed pharmaceutical companies? Empirical tests based on double difference model

Abstract: Introduction: The normalized implementation of the centralized volume-based procurement policy for pharmaceuticals is a concerted push for supply-side structural reform of the pharmaceutical industry in China. The impact of the centralized drug procurement policy on pharmaceutical companies' transition from imitation to innovation is investigated to test whether a positive effect occurs in the innovation landscape of the pharmaceutical market. Methods: The double difference method and a series of robustness te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Therefore, this quasi-natural experiment model can effectively conduct quantitative evaluations and has been widely applied in the field of public health policy evaluation in recent years ( 55 ). Some scholars have already used the DID model to empirically study changes in profitability, financial performance, and innovation performance of enterprises before and after the implementation of the NCDP policy ( 23 , 56 , 57 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this quasi-natural experiment model can effectively conduct quantitative evaluations and has been widely applied in the field of public health policy evaluation in recent years ( 55 ). Some scholars have already used the DID model to empirically study changes in profitability, financial performance, and innovation performance of enterprises before and after the implementation of the NCDP policy ( 23 , 56 , 57 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is scarce literature that explores the impact of the NCDP policy on enterprises’ R&D investment from the perspective of stakeholders. Most of previous research focus on theoretical analysis ( 19–21 ) and lack empirical studies ( 22 , 23 ). From the theoretical perspective, scholars have conflicting views.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Liu et al ( 23 ) applied the difference-in-differences model to find that the generic consistency evaluation policy has a positive impact on the innovation quality of the Chinese pharmaceutical industry. Gu et al ( 24 ) adopted listed medicine companies in the Shanghai and Shenzhen A-share markets as samples and empirically found that centralized drug procurement policy has a significant improvement on the quality of medicine innovation. In addition, the qualitative evaluation of medicine innovation policies in existing research mainly concentrates on the specific interpretation of policy content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…China's pharmaceutical policies have been introduced intensively to address this industry's special status. The Drug Administration, National Health Insurance Administration, and National Health and Health Commission are linked to reform and have been adjusting the base drug catalog, piloting DRG/DIP payment reform (2), promoting health insurance and health insurance fund reform, improving the traceability system and medical device management, carrying out the consistent evaluation of generic drug quality and efficacy, and organizing several national centralized drug volume-based procurements (3). The government encourages enterprises to research and develop innovations to improve quality and efficiency.…”
Section: Introductionmentioning
confidence: 99%